2009
DOI: 10.3892/ijo_00000280
|View full text |Cite
|
Sign up to set email alerts
|

Role of V-ATPases in solid tumors: Importance of the subunit C (Review)

Abstract: Abstract. Acidity is one of the main characteristics of OSCC (oral squamous cell carcinoma) as a solid tumor. The VATPase is the primary regulator of the tumor microenvironment, by means of proton extrusion to the extracellular medium. The decrease in extracellular pH confers the cells a resistant, highly invasive and metastatic phenotype. However, the acid medium confers an optimum pH to the degradative enzymes (such as proteases and MMPs) for their proper functioning. The C subunit (ATP6V1C) of V1 intra-memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 76 publications
1
26
0
Order By: Relevance
“…The present study indicated that rabeprazole, a second-generation PPI, could efficaciously induce apoptosis in human gastric cancer cells by blocking the intracellular proton extrusion, thus supporting the idea of PPIs as a potential treatment for gastric cancer (16,17). Highly proliferative cancer cells produce a large amount of H + generated by aerobic glycolysis, lactic acid production and proton extrusion, leading to a lower extracellular pH level compared with normal tissues (18,19).…”
Section: Discussionsupporting
confidence: 78%
“…The present study indicated that rabeprazole, a second-generation PPI, could efficaciously induce apoptosis in human gastric cancer cells by blocking the intracellular proton extrusion, thus supporting the idea of PPIs as a potential treatment for gastric cancer (16,17). Highly proliferative cancer cells produce a large amount of H + generated by aerobic glycolysis, lactic acid production and proton extrusion, leading to a lower extracellular pH level compared with normal tissues (18,19).…”
Section: Discussionsupporting
confidence: 78%
“…The future of these molecules in cancer treatment involves measuring the overexpression of specific V-ATPase subunits in tumors to be treated and then using inhibitors specific for the subunits being expressed in a synergistic approach. This will allow clinicians to provide more specific treatment, while also minimising adverse effects (Perez-Sayans et al, 2009a,b, 2010.…”
Section: Discussionmentioning
confidence: 99%
“…How PKA could be exerting its influence on assembly is still not clear. Subunit C is considered by some authors one of the principal regulators of the assembly and disassembly of the holoenzyme [45]. Accordingly, work by Voss et al has shown a direct phosphorylation of subunit C by PKA that could influence V 1 /V 0 assembly [46,47].…”
Section: Structure Of V-atpasesmentioning
confidence: 98%